Tactics of Surgical Treatment of Wounded with Gunshot Injuries of the Upper Limb in Modern Conditions - Strafun, S.S.; Kurinnyi, I.M.; Borzykh, N.O.; Tsymbaliuk, Ya.V.; Shypunov, V.G. (TERRA ORTHOPAEDICA, 2021)
Summary. Our study aimed to optimize the tactics of surgical treatment of wounded with gunshot wounds of the upper extremity by determining the factors influencing the outcome of treatment of servicemen in modern conditions of specialized and highly specialized medical care.Materials and Methods. Surgical treatment of 123 patients with gunshot wounds of the upper extremity who were treated at the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine” and the National Military Medical Clinical Center “Main Military Clinical Hospital” of the Ministry of Defense of Ukraine was analyzed. The mean age of patients was (35.3±8.7). At the level III of medical care, the largest share was occupied by wound closure (28.0%) and surgeries on the skeletal system (6.7%). At the level IV of medical care, the largest share was occupied by surgical procedures for closing unhealed wounds – 28%, due to the consequences of gunshot nerve injuries – 11.5%, fractures – 10.7%, and restorative interventions on muscles – 5.5%.Results. By calculating the odds ratio (Odds Ratio, OR), it was found that the presence of compartment syndrome reduces the probability of obtaining a positive result by 11 times (OR=11.3), and late treatment at the level IV of care reduces the effectiveness of treatment by 9 times (OR=9.1). In the group of patients with peripheral nerve damage, satisfactory results were 6.9 times less than in the group without such damage (OR=6.9); the presence of a tissue defect worsened the prognosis of treatment by almost 5 times (OR=4.7). The average time to start surgical treatment after a gunshot wound was 2.8±5.0 days at the level III and 47.2±70.4 days at the level IV. It was found that for patients admitted to the level IV facilities for up to 30 days, the percentage increase in upper extremity function was 42.6±11.8 after treatment and 28.5±10.0 at a later start of treatment.Conclusions. The results of the study of the factors influencing the outcome of treatment prove the need for early (up to 3 weeks) admission of wounded with gunshot wounds to the level IV of medical care.